Evaluation of Abulyatama University Website Quality With an Importance Performance Analysis (IPA) Approach Based on Webqual 4.0 - Nur’aina (International Journal Education and Computer Studies (IJECS), 2021)
The website plays an important role in academic activities such as filling out the Study Plan Card (KRS) and academic schedules. The Abulyatama University website also serves to convey the information needed by students from the university. Given the importance of the role of the Abulyatama University website, it is necessary to carry out an evaluation, especially to find out how the quality of the website is, evaluating the quality of the Abulyatama University website by using an Importance Performance Analysis (IPA) approach based on WebQual 4.0. The author will apply the Webqual 4.0 method to find out the difference (gap) between actual perceptions and ideal user expectations as measured by the dimensions of information quality, service interaction quality, user interface quality, and usability). Each of these variables will be used to define the purpose of the assessment of a questionnaire on the object of the questionnaire. Based on the research that has been done, several conclusions have been drawn, namely; the results of the analysis of the average value of the level of expectation or importance for the average value of usability on the Abulyatama University website is 3.68, information quality is 3.70, and on service, interaction is the result of an analysis of the level of importance and level of performance, the things that are prioritized for improvement are in quadrant I. quadrant I show the attributes that are considered important by students, but the website manager of Abulyatama University has not provided it optimally or well to students. These attributes are the display according to the type of website (U1), providing reliable information (IQ1), providing fairly detailed information (IQ4), and providing relevant information on the existence of a community atmosphere (SIQ4), and (SQI4), ease of attracting interest and attention (SIQ5), and ease of communication (SIQ6). From these attributes, the manager of the Abulyatama University website must pay attention to so that consumers feel more satisfied and loyal in accessing the information on the Abulyatama University website.